A COVID-19 Risk Reduction Strategy for the Treatment of Acute Vogt-Koyanagi-Harada Disease Utilizing the Antiviral Potential of Cyclosporine. (7th February 2023) - Nakayama, Makiko; Okada, Annabelle A; Hayashi, Isami; Ando, Yoshimasa; Watanabe, Takayo; Keino, Hiroshi
ABSTRACT: Purpose: To report on the successful treatment of patients with acute Vogt-Koyanagi-Harada (VKH) disease utilizing the antiviral potential of cyclosporine during the COVID-19 pandemic. Study Design: Case series. Methods: Clinical records were retrospectively reviewed of 4 patients presenting with new-onset acute VKH disease who elected to receive initial treatment consisting of bilateral sub-Tenon injection of triamcinolone acetonide combined with immediately starting oral cyclosporine without the use of systemic corticosteroids. Results: The mean follow-up was 17.0 months. Choroidal thickness decreased to normal with recovery of bilateral best-corrected visual acuity (BCVA) of 1.2 in 3 patients. One elderly patient had decreased BCVA (OD 0.5, OS 0.8) due to cataract progression and mild epiretinal membrane. No recurrences of intraocular were observed in any patients. Mild renal dysfunction developed in 2 elderly patients, but importantly no patients developed COVID-19 disease. Conclusions: Oral cyclosporine as the initial systemic treatment of acute VKH disease, in combination with sub-Tenon injection of triamcinolone acetonide, lead to favorable clinical outcomes. Due to the known antiviral properties of cyclosporine, we suggest that this may represent a good treatment strategy for patients during the COVID-19 pandemic.